The Optimum design of arch dam shape using Particle Swarm optimization algorithm - seyed reza mousvi; نادر برهمند; Akbar Ghanbari; Arash Totonchi (مهندسی منابع آب)
Introduction: Considering the effects of building dams in downstream basins, the need to investigate their condition and effects is one of the important issues. In this study, the optimal form of concrete double-arched dams was investigated under various interactions against earthquakes. Methods: The volume of concrete used was considered as the goal function of the optimization problem and the design variables were the geometric parameters of the dam. The twenty geometrical parameters were investigated. First, the dam-water-foundation system was simulated using the finite element method. Then the optimization was done using the particle swarm optimization (PSO). Results: To check the performance of the method used to optimize arch dams, the Moropont dam was selected as a real structure and optimized under different conditions against the Centro earthquake. The calculation parameters of the PSO algorithm showed the proper performance of this algorithm. Conclusion: To check the random nature of the optimization algorithm, four independent executions were performed for the PSO method and their results were analyzed separately. The results showed that with the number of 10,000 analyzes, the volume of concrete used was equal to 346,000 m3.